2008
DOI: 10.4265/bio.13.97
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Bacterial Community Found in Sammanarezushi (Saury Narezushi Revealed by the 16S rRNA Gene Clone Library

Abstract: Narezushi is one of Japanese traditional foods and is made by fermenting salted fish meat and cooked rice together. In this study, the microbial diversity of samma-narezushi (narezushi using saury, Cobolabis saira) was analyzed by the 16S ribosomal RNA gene (rDNA) clone library. Randomly selected 89 clones were sequenced and phylogenetically analyzed. The sequences were classified into 12 operational taxonomy units (OTUs) at the 97% identity threshold.Most of the clones (89%) were lactic acid bacteria (LAB) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Recently, we have published a microbial diversity analysis of samma-narezushi (narezushi of saury) by using the 16S rDNA clone library technique. We also demonstrated the usefulness of this technique in analyzing microbial diversity in narezushi (Matsui et al 2008). Our results showed that Lactobacillus sakei is the main organism involved in the fermentation of samma-narezushi.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Recently, we have published a microbial diversity analysis of samma-narezushi (narezushi of saury) by using the 16S rDNA clone library technique. We also demonstrated the usefulness of this technique in analyzing microbial diversity in narezushi (Matsui et al 2008). Our results showed that Lactobacillus sakei is the main organism involved in the fermentation of samma-narezushi.…”
Section: Introductionmentioning
confidence: 67%
“…The rice portion has a slightly higher lactic acid composition than fish meat. We have reported the chemical composition of narezushi in the meat of saury fish (samma-narezushi) (Matsui et al 2008). The nutrient composition of samma-narezushi was as follows: 19.7% protein, 3.9% lipid, and 3.5% carbohydrate in fish meat, and 2.5% protein, 0.1% lipid, and 18.1% carbohydrate in rice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations